Pondok Pesantren Perkampungan Minangkabau 2013-2020 - Yoga Pratama; Erniwati Erniwati (Jurnal Kronologi, 2021)
Abstract This article is a historical study of the Perkampungan Minangkabau Islamic Boarding School 2013-2020. The study, in particular, aims at describing the development of the Perkampungan Minangkabau Islamic Boarding School. This article uses the historical method of the process by using source documents belonging to the Minangkabau Islamic Boarding School such as the deed of establishment, the curriculum as well as interviews with the founders, teachers and staff of the Minangkabau Village Islamic Boarding School and also with the community around the Perkampungan Minangkabau Islamic Boarding School. The findings of the research shows this study indicate that the Perkampungan Minangkabau Islamic Boarding School was founded by the Shine Al Falah Foundation in 2013 due to problems with the development of the Dhuafa Nusantara Islamic Boarding School managed by the Bakti Nusantara Isafat Foundation. Development of Perkampungan Minangkabau Islamic Boarding School can be seen from 2 phases with the change of location of the Perkampungan Minangkabau Dhuafa Islamic Boarding School. The students originally came from the Al Falah Orphanage and increased from outside the orphanage. The financing of Islamic boarding schools relies on donor assistance and is managed by the amil zakat institution assisted by the Shine Al Falah Foundation. Keyword: Islamic Boarding School, Dhuafa, Deveploment Abstrak Artikel ini merupakan kajian sejarah mengenai Pondok Pesantren Perkampungan Minangkabau dari tahun 2013-2020. Tujuan dari artikel untuk mendeskripsikan perkembangan Pondok Pesantren Perkampungan Minangkabau tahun 2013-2020. Artikel ini menggunakan metode sejarah dari proses dengan menggunakan sumber dokumen-dokumen milik Pondok Pesantren Perkampungan Minangkabau seperti akta pendirian, jumlah santri, kurikulum serta wawancara dengan pendiri, guru dan staff Pondok Pesantren Perkampungan Minangkabau dan juga dengan masyarakat sekitar Pondok Pesantren Perkampungan Minangkabau. Hasil dari artikel ini menunjukan bahwa Pondok Pesantren Perkampungan Minangkabau didirikan oleh Yayasan Shine Al Falah pada tahun 2013 karena adanya permasalahan pengembangan Pondok Pesantren Nusantara yang di kelola Yayasan Bakti Nusantara Isafat. Perkembangan dari Pondok Pesantren Perkampungan Minangkabau bisa dilihat dari 2 fase dengan perpindahan lokasi Pondok Pesantren Perkampungan Minangkabau. Santri Pondok Pesantren Perkampungan Minangkabau awalnya berasal dari panti Panti Asuhan Al Falah dan bertambah dari luar panti asuhan. Dalam pembiayaan pondok pesantren mengandalkan bantuan donatur dan dikelola oleh lembaga amil zakat binaan Yayasan Shine Al Falah. Kata Kunci: Pondok Pesantren, Dhuafa, Perkembangan